Olive-mill and grape-mill residue impact the growth, physiology and nutrient status of grapevines young cuttings - Tzortzakis, Nikos G.; Chrysargyris, Antonios (My University, 2024)
Olive tree and grapevines cultivation is expanded in the Mediterranean area, revealing high yields for both crops but processes that follow harvesting (olive oil and wine production) create residues with high constraints on their effects on the environment and human health. The present study aimed to examine the possible utilization of olive-mill residues (OMR) and grape-mill residues (GMR) at 15% v/v in soil to grow international (Syrah) and indigenous (Xynisteri) grapevines cultivars. The adding of OMR and GMR in soil increased electrical conductivity and nitrogen content but decreased pH of the mixtures. In Xynisteri, chlorophylls were remained unaffected, but total phenols, antioxidant capacity and flavonoids were decreased by adding OMR and GMR in soil. Malondialdehyde (MDA) as a stress indicator for lipid peroxidation was high in Xynisteri at soil and 15% OMR but decreased at 15% GMR, while similar reduced values were found for hydrogen peroxide at the same treatment. Nitrogen was accumulated more at GMR-treated plants in both Xynisteri leaves and roots. Syrah plants grown in OMR- or GMR-media had decreased chlorophylls content but increased total phenols and antioxidant content. OMR stimulated flavonoids in leaves comparing to GMR and control in Syrah. MDA was increased at GMR-treated Syrah plants. It can be concluded, that both GMR and OMR have the potential to be mixed with soil, providing minerals and organic matter to the mixtures but further research is required to obtain the appropriate fertigation scheme when using plant residues, avoiding any possible plant stress and/or nitrogen mobilization by microorganisms.
Keywords: Antioxidants; Minerals; Olea europaea residues